BACTERIAL ETIOLOGY AND THEIR ANTIBIOGRAMS IN COMMUNITY ACQUIRED URINARY TRACT INFECTIONS WITH SPECIAL CONSIDERATION ON STERILE PYURIA - SAEED, ALI YAHYA (Journal of Duhok University, 2023)
Urinary tract infections are caused by heterogenous etiological agents and high proportions of samples are without significant growth. Antibiotic resistance issue constitutes a major public health problem. A retrospective study was conducted from a period of January,2021 to May 2023 in which a total of 419 mid urine samples were collected. The ages were ranged from 4 months to more than 65 years. Adults were 348 (83.1%) and children were 71 (16.9%). Females were 358 (85.5%) and Males were 61 (14.5%).  From 419 samples 193 (46.3%) were normal (pus cells < 5/HPF), while 225 (53.7%) were abnormal (Pus cells >5/HPF). Among 225 abnormal samples, 100 (44.5%) showed no growth, while 125 (54.5%) yielded significant growth. Among males 21/ 123 (17%) of the samples showed growth compared to 102 /123 (83%) in females. Among the isolated pathogens, E. coli was the predominant (71%) followed by Staphylococcus aureus (14%), Streptococcus spp. (6%), Proteus spp. (5%), Pseudomonas aeruginosa (3%) and Klebsiella pneumoniae (1%). High percentages of total UTIs and E. coli were found among age group 20-30 years. The highest percenatge of resistant was against doxycycline  (87.61%)  followed by trimethorprim (86.66%), cephalothin (86.06%), ceftriaxone (60.97%), amoxyclav (57.02%), ciprofloxacin (41.22%) while the  lowest resistant was against Amikacin (25.2%) followed by Gentamicin (34.14%), nitrofurantoin (37.39%).